RESPONSABILIDADE SOCIAL E SUSTENTABILIDADE DOS FUNDOS DE PENSÃO BRASILEIROS MODELO DE AVALIAÇÃO - Santiago, Ricardo Domingues (2009)
In the last years, the pension funds have been seen as inductors of the insertion of governance and social responsibility into organizations, in which they invest and/or become related to, with a great impact on the market. In such case, through a descriptive and exploratory research, this work intends to analyze the behavior of the brazilian pension funds, specifying the current practices of corporate accountability adopted by those entities, and also seeking for identify if the increasing performance as socially responsible investors is being followed by a corresponding development of the levels of accountability in all their operational activities and relationship dimensions. Thus, using a conceptual model of social entrepreneurial performance evaluation, searched in bibliographical revision, it is expected to evidence, in the end of this work, that the searched pension funds, besides acting as socially responsible institutional investors, present a socially responsible attitude before their public of multiple interests (participants, employees, suppliers, community, etc).